Toddler's Monitoring Application Toward Growth And Development Of Food Supply - Maharani, Nurul Indah, Hernawan Slistyanto, S.T, M.T (2017)
Nutrition is chemical component which is contained in food substances.Nutritional status of toddler is one of indicators that reflect level of social welfare.Now a days, there are many malnourished because mothers who do not understand how many calories should be given to their toddlers to support childhood development. Every toddler gets different number of calories depending on his age and body weight and body height. Many toddlers not breastfeed by their mother. Breastfeeding should be given to toddlers at ages do 0 to 2 years. Breastfeeding is given as the main food for toddlers, in early 6 month of their life and 7 to 24 months it requires food additive. Therefore, we need an application that can find out how many calories which are needed for their toddlers. Toddlers will get different number of calories based on their age and body weight and body height. What kind of food supply contains enough calories for their toddlers, and how to calculate in order to get enough calories for them. Therefore, once made this application can help the wider community, especially the mothers who do not understand about knowing how many nutrition, caloric and food supplywhich is needed by their children. Keywords: Nutritional, Nutrition Calculator